1999
DOI: 10.1115/1.556273
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Analysis of Direct Steam Generation Solar Collectors

Abstract: Direct steam generation collectors are considered with the aim to improve the performance of a parabolic trough collector leading to a reduction of operating costs of solar electric generation systems. In this study a hydrodynamic steady state model is developed and linked with a thermal model to optimize the performance of once-through direct steam generation solar collectors. The hydrodynamic model includes flow pattern classification and a pressure drop model. Flow pattern maps for typical DSG collectors wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…29 Figure 7 shows the pressure drop variation with flow rate in DSG and oil-based collector tubes [28]. The flow rate in DSG collector tubes determines the two-phase flow patterns and the contribution of each phase to the total pressure drop.…”
Section: P R E S S U R E D R O Pmentioning
confidence: 99%
See 3 more Smart Citations
“…29 Figure 7 shows the pressure drop variation with flow rate in DSG and oil-based collector tubes [28]. The flow rate in DSG collector tubes determines the two-phase flow patterns and the contribution of each phase to the total pressure drop.…”
Section: P R E S S U R E D R O Pmentioning
confidence: 99%
“…Previous studies [27][28][29] have suggested a model for predicting flow transitions in horizontal two-phase flow, considering stratified flow with a wave existing on the surface. As the gas accelerates, the pressure in the gas phase decreases and the wave grows.…”
Section: F L O W P a T T E R N Smentioning
confidence: 99%
See 2 more Smart Citations
“…Benefits to the OT de sign are elimination of the steam separation and transport equip ment, though this arrangement introduces the possibility of flow and heat transfer instability. OT flow has been proposed for linefocus CSP [21][22][23], but has not yet been demonstrated because of control complexity [24].…”
Section: Steam Flow Configurationmentioning
confidence: 99%